Effect of Nanomaterials on Tribological and Mechanical Properties of Polymer Nanocomposite Materials. (31st May 2022) - Kumar, M. S. Senthil; Selvan, Chithirai Pon; Santhanam, K.; Kadirvel, A.; Chandraprabu, V.; SampathKumar, L.
Abstract : The good adhesion and interfacial interaction between the nanomaterial and the matrix show that the low content polymer nanocomposite has better tribological and mechanical properties such as strength, modulus, fracture toughness, and fatigue properties. This phenomenon has attracted the attention of many researchers in this field for the past two decades. Nanomaterials are available in many forms, such as nanotubes, nanoclays, nanofibers, nanoparticles, and graphene depending on the shape. This article summarizes the mechanical test results of different nanocomposite materials under various operating conditions. In addition, the current research clearly describes various decisive factors that affect material properties, such as the dispersion of nanoparticles, clay tactoids, processing conditions, agglomeration, and distribution status. The tribological properties and fatigue resistance of nanocomposites are also discussed in this study. In addition, the article also discusses the related issues of incorporating nanomaterials into the matrix.